Penerapan Media Pembelajaran Interaktif untuk Meningkatkan Motivasi dan Hasil Belajar IPS - Maria Theresia Ambarwati Sulistyorini; Salamah Salamah (UM Purwokerto Press, 2022)
The rapid development of science and technology today causes the flow of information to be fast and without limits. This allows all parties to obtain information quickly, easily, and abundantly from various sources and places where they are located. The purpose of this study was to determine the effect of interactive learning media on increasing students' motivation and learning outcomes on the content of Social Sciences (IPS) lessons and so that teachers can learn more concrete information that is abstract. This study used an experimental method, carried out in class V SD Negeri 1 Kutoarjo, and the sample was taken as many as 38 students. The results showed an increase in learning motivation of 0.74 with high interpretation, critical thinking ability of 0.72 with high interpretation, and student learning outcomes of 0.35 with medium category. The application of interactive learning media can increase the motivation and learning outcomes of fifth graders at SD Negeri 1 Kutoarjo for Social Studies Lessons.